Characterisation of microRNA expression profiles of Vitis vinifera in response to grapevine leafroll-associated virus 3 infection - Aldrich, Dirk Jacobus (Stellenbosch : Stellenbosch University, 2017., 2017)
Thesis (MSc)--Stellenbosch University, 2017.